Enhancing Knowledge through Archaeology and Epigraphy: Research and Development - IIK ARIFIN MANSURNOOR (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2016)
This paper aims to locate the research potential and necessity of monuments within the study of archaeology and epigraphy. Leading to that it is important first to give the backgrounds and development of the two disciplines  in this country. Thus, some brief presentations of the more recent works will hopefully serve the purpose. From here, the paper will focus on the current findings of the research on Islamic monuments. Unlike archaeological works, monuments will be more democratic as they include diverse builders, beyond the formal and the powerful.Atcheology